MEKANISME DAN DASAR KEBERLAKUAN LEGAL DRAFTING DI INDONESIA - Rahmasari, Betha (Istinbath : Jurnal Hukum, 2016)
Indonesia is a country based on pancasila and the Constitution of the Republic of Indonesia in 1945, then all aspects of life, civic, State, and national Government should be included based on the law. With regard to the process of the formation of laws, both prior to and post the amademen Constitution, and after the establishment of Act No. 10 of 2004, senyatanya is still faced with various problematic, both substantially juridical, technical authors, as well as the implementation and enforcement of the law. The publication of law No. 10 of 2004 which was approved in a plenary meeting of the DPR on 24 May 2004 and was replaced by law number 12 of the year 2011 on the establishment of regulations, then the mechanism of the formation of laws and regulations have been terintegritas in one act. Planning laws-laws at least contains five things: 1. the planning and goals of the Foundation, 2. Application priority legal matter will be planned, 3. Determination of the mechanisms of the planning process, 4. A means of planning, and 5. supporting, such as research, extension, dekumentasi, and so on. Legislation is a decision of a State agency or agencies of Government that was formed on the basis of attribution and delegation. In another formulation can also be interpreted, that laws are regulations written legislation formed by State agencies or officials who authorized and binding in General. In the study of the science of law there are three factors that become a parameter of legislation so as to apply properly, i.e. have basic juridical, sociological, enforceability and philosophical. Through this mechanism the formation and enactment of laws and regulations in Indonesia parsed systematically.